The Building Façade Renovation Guideline for Developing Urban Tourism in Old Town Nong Khai - Pattananurot, Pakorn (Journal of Architectural/Planning Research and Studies (JARS), 2020)
The old town Nong Khai is an important economical area for decades. The architectural characteristics of the buildings were especially built to support the commercial and rescidential activities. The purposes of this research are 1) to acquire a guideline for renovating the façade and 2) to propose a model and routes of tourism in the old town based on not only relevant documents, research papers, field data, an observation, but also an interview. The results revealed the guideline into two group for the renovation of façade were the building influenced by French colonial style should conserve the façade as much original as possible with new utilities, and the modern style building should originate the design. In term of tourism in the old town enabled a route of cultural tourism and a route of the local products and souvenir. To link the community with adjacent tourist attractions, bicycle’s routes were likely proposed. The renovation of the façades in the old town of Nong Khai. Contributes the conservation in term of the accomplished technicians and the material used, as well as, the renovation guideline for others cultural tourist attractions.